Translingual competence and study abroad: shifts in sojourners' approaches to second language learning. (2nd September 2020) - Kang, Hyun-Sook; Pacheco, Mark Barba
Abstract: While study abroad (SA) has long been considered an opportunity for language learning, relatively little research has investigated how short-term SA programs hosted by Anglophone countries support varied aspects of sojourners' language learning. To address this gap, the current study examined how 10 college students from a Korean university developed translingual competence (Canagarajah 2014 ) while participating in a 4-week program hosted by a US Midwestern university. This study explored the ways in which individual sojourners developed their knowledge of semiotic resources and awareness of these resources in relation to communicative situations afforded by the SA program. Data, including bi-weekly written sojourner reflections, mid-program focus group interviews, individual interviews at the program's conclusion, questionnaires before and after the program, participant-observer notes, and other artifacts, were analyzed, using a cross-case study design (Stake 1995 ). Sojourners demonstrated their understandings of (1) how resources relate to aspects of their identities and those of their interlocutors; (2) how resource use was shaped by their local placements and they could shape aspects of their environments to accommodate resources; and (3) how English linguistic resources could be encoded to facilitate communication during SA. The implications of these findings are further discussed for SA program development.